2011
DOI: 10.1590/s1516-35982011000300029
|View full text |Cite
|
Sign up to set email alerts
|

Performance of finishing beef cattle fed different diets containing whole-crop maize silage or sugarcane silage

Abstract: -The objective of the present study was to evaluate the performance of beef cattle in feedlots fed diets containing either whole-crop maize silage or sugarcane silage, and with different formulations. Five diets were evaluated:MSF -diet containing whole-crop maize silage, with fixed formulation during feedlot period; MSV-diet containing wholecrop maize silage, with variable formulation according to feedlot phase; SCSF -diet containing sugarcane silage with fixed formulation; SCSV-diet containing sugarcane sila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
1
6
1
4
Order By: Relevance
“…However, a feed conversion of 4.77 was observed, which is better than that reported in the current study. In another study, Roman et al (2011) observed higher average values for DWG and feed conversion (1.39 and 7.7 respectively), and similar values for HCD for sugarcane silage. The carcass gains (kg/day) were approximately 26% greater (0.65 × 0.52) for the animals fed on sugarcane in natura than the diets with ensilaged sugarcane (Menezes et al, 2011).…”
Section: Resultsmentioning
confidence: 70%
“…However, a feed conversion of 4.77 was observed, which is better than that reported in the current study. In another study, Roman et al (2011) observed higher average values for DWG and feed conversion (1.39 and 7.7 respectively), and similar values for HCD for sugarcane silage. The carcass gains (kg/day) were approximately 26% greater (0.65 × 0.52) for the animals fed on sugarcane in natura than the diets with ensilaged sugarcane (Menezes et al, 2011).…”
Section: Resultsmentioning
confidence: 70%
“…Dessa forma, busca-se o conhecimento do valor nutritivo dos alimentos, que pode ser obtido através da composição química, de digestibilidade e pelo próprio desempenho animal, e a partir daí a formulação de dietas balanceadas que possibilite uma melhor eficiência alimentar. Nesse contexto, estudos comprovam que a cana-de-açúcar apresenta resultados promissores com base em índices produtivos e econômicos (Queiroz et al, 2008;Pinto et al, 2010;Romam et al, 2011), todavia pode tornar-se uma realidade alimentar para caprinos leiteiros. Ainda são incipientes os trabalhos encontrados na literatura utilizando-se a cana-de-açúcar como volumoso para esses animais.…”
unclassified
“…Estudos prévios com vacas leiteiras também reportaram que o maior consumo de MS ocorreu nas primeiras quatro horas após o fornecimento da ração fresca no comedouro (Bhandari et al, 2008, Carvalho et al, 2012 Não houve resposta (P>0,05) da fonte de forragem sobre o PC em todo o período experimental (Tabela 5), reforçando a hipótese de que a fonte de forragem não exerce influência sobre o desempenho animal, desde que os níveis nutricionais das dietas sejam semelhantes. Em outros estudos, o ganho de peso diário e o PC pré-abate também não foram alterados pela fonte de forragem (Fernandes et al, 2007), mesmo quando os níveis de FDN e CNF na dieta à base de SM foram respectivamente menores e maiores em relação à dieta com SC (Roman et al, 2011), o que teoricamente poderia resultar no maior ganho de peso nos animais alimentados com SM. Horas pós-alimentação EPM 5…”
Section: Resultsunclassified